DAMPAK PENGGUNAAN PESTISIDA DALAM KEGIATAN PERTANIAN TERHADAP LINGKUNGAN HIDUP DAN KESEHATAN - Sinambela, Bilker Roensis (Percetakan Umi Toaha Makassar, 2024)
Pesticides are chemicals whose use is close to human life. Agricultural systems based on high-energy input materials such as chemical pesticides can cause environmental pollution, especially in the agricultural environment. Inappropriate use of pesticides endangers the health of farmers, consumers, and non-target microorganisms and has an impact on environmental pollution both soil and water. Data collection techniques with secondary data collection methods, where the author collects 10 articles and then processes the data into new data. The results showed that when the behavior and use of pesticides were classified as good criteria with a score of 65.9%, the environmental impact was also classified as good criteria. The impact of the use of pesticides found in farmers is in the form of nausea, vomiting, dizziness, and itching on the skin. Of the 100 samples, most of them, 75%, experienced these health problems. The impact of using pesticides in agricultural activities on the environment and health can have good and bad effects depending on how the attitudes and behavior of farmers in using pesticides. Excessive use of pesticides, and not following applicable regulations will cause pollution to the environment (soil pollution, water pollution, and wild organisms and animals) and health problems that interfere with the physical condition of the farmers themselves such as dizziness, nausea, and others, this is due to farmers who tend not to use personal protective equipment (PPE) when interacting with pesticides.